Civic and Uncivic Values in Macedonia - Ramet, Sabrina P. author. aut Link
XV, 347 p.
Keywords: One of the central challenges facing Macedonia, along with other Yugoslav successor states, is to develop civic values and to combat such uncivic values as ethnic intolerance, religious bigotry, and homophobia. This volume brings together specialists in Macedonian affairs to offer insights into the experiences and values of the Macedonians.